Developing continuous submicron-scale conductive interpenetrating hydrogel network in polyethylene matrices through controlled crazing and polymerization - Kornberg, Anton; Thompson, Michael; Zhu, Shiping (Industrial and Engineering Chemistry Research, 2020)
An approach is described for the synthesis of controlled submicron interpenetrating networks with distinct functional features in commodity polymers, based on a mechanism of crazing and polymerization. In this work, ion conductivity was introduced into polyethylene with only minor losses in its mechanical properties, using a highly branched acrylic hydrogel. Control over the porous network developed in the matrix was gained by the addition of a crystallizing nucleating agent, which was used to increase the number and reduce the size of crystallites. Variation of experimental conditions, such as the degree of elongation and applied reaction pressure, produced different morphologies and conductivity for the co-continuous alloy. The samples were deformed in a liquid medium that possessed an affinity for the matrix material, and acted both as a surface-active agent for the crazing, and as a reactant for the conductive phase. Without pressure, deforming by 100% strain yielded a conductivity of 5.67×10⁻⁷ S/cm for the polymer specimen. Simultaneously increasing system pressure while constantly straining a specimen enabled further enhancements in conductivity. As a particular example, elongation of 100% and applied pressure up to 2.76 MPa ensured conductivity nearly equal to that of the pure hydrogel at 4.43×10⁻⁴ S/cm.